Translation of conceptual metaphors in economic texts / Zalifah Rozalina Azman Aziz - Zalifah Rozalina, Azman Aziz (2019)
The current study explores metaphorical expressions found in specialized economic text of the English source language and the translations into the Malay target text. The study aims to reveal the main conceptual metaphors underlying these metaphorical expressions and the translation strategies employed to translate them. The conceptual metaphor theory proposed by Lakoff and Johnson (1980) and expanded by Kovecses (2010) is applied as the principal theoretical framework to analyse the metaphorical expressions in the selected data. The semantic field theory of metaphor put forth by Kittay and Lehrer (1981) is used to identify and group the source domains and target domains of the conceptual metaphors, while the metaphor identification procedure (MIP) proposed by the group of researchers who called themselves the Pragglejaz Group (2007, cited by Kovecses, 2010) is applied to identify the metaphoricity of the metaphorical linguistic expressions found in the data. The selected data is the Bank Negara Malaysia annual report of 2016, the most recently published report of Bank Negara at the time this thesis began. The choice of data is based on its technicality in the field of economics, containing many specialised metaphors and jargons which pose challenges to translators and the authenticity of the report. Translation strategies proposed by Schäffner (2004, 2014) for conceptual metaphor translation which have been adapted by Alshunnag (2016) and Tcaciuc (2013) are applied to analyse the translation strategies of the English metaphors into Malay. Qualitative textual analysis is used to discern the metaphorical expressions while translation strategies are identified by juxtaposing the source text against the target text. The findings show that the HUMAN BEING, MACHINE and BUILDING conceptual metaphors are the most frequently used cognitive metaphors used in the economic text, and retaining the conceptual metaphor from English into the Malay target text through literal translation is the most frequently employed strategy to translate conceptual metaphors.